2001
DOI: 10.1046/j.1365-246x.2001.00453.x
|View full text |Cite
|
Sign up to set email alerts
|

Finite source modelling of magmatic unrest in Socorro, New Mexico, and Long Valley, California

Abstract: SUMMARY We investigate surface deformation associated with currently active crustal magma bodies in Socorro, New Mexico, and Long Valley, California, USA. We invert available geodetic data from these locations to constrain the overall geometry and dynamics of the inferred deformation sources at depth. Our best‐fitting model for the Socorro magma body is a sill with a depth of 19 km, an effective diameter of 70 km and a rate of increase in the excess magma pressure of 0.6 kPa yr−1. We show that the correspondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 45 publications
5
46
1
Order By: Relevance
“…Hooper et al [7] unwrapped PS time series over Long Valley using a 2D algorithm and also found the unwrapping between the two benchmarks to be reasonable. However, the overall pattern of the displacements found by Hooper et al [7] differs to that observed by Fialko et al [28], especially on the west side of the caldera where there appears to be a discontinuity in the former data set. The overall pattern we find using the stepwise 3D algorithm, on the other hand, matches well.…”
Section: Long Valley Insar Persistent Scatterer Examplecontrasting
confidence: 76%
“…Hooper et al [7] unwrapped PS time series over Long Valley using a 2D algorithm and also found the unwrapping between the two benchmarks to be reasonable. However, the overall pattern of the displacements found by Hooper et al [7] differs to that observed by Fialko et al [28], especially on the west side of the caldera where there appears to be a discontinuity in the former data set. The overall pattern we find using the stepwise 3D algorithm, on the other hand, matches well.…”
Section: Long Valley Insar Persistent Scatterer Examplecontrasting
confidence: 76%
“…In both cases, the modeled source of inflation is smaller than the seismically imaged magma body (22). There is indication of subsidence around the central uplift due to the SMB (10,21,22), although the rates of both uplift and subsidence due to the SMB are smaller than those due to the Altiplano-Puna Magma Body and therefore subject to greater uncertainties (Fig. 3).…”
Section: Yuri Fialko* and Jill Pearse †mentioning
confidence: 93%
“…Successful geophysical applications of classical differential InSAR have started from avoiding error quantification [ Massonnet et al , 1995; Fialko and Simons , 2001] to gradually incorporate some error assessment [ Simons et al , 2002; Knospe and Jonsson , 2010]. Several authors have suggested how to incorporate estimated observational errors for the extraction of geophysical parameters (magma volume, earthquake source parameters, etc.)…”
Section: Introductionmentioning
confidence: 99%